Matched ebook - Condie, Ally (Matched Trilogy, 2012)
#1 New York Times Bestseller “[A] superb dystopian romance.” – The Wall Street Journal   “Strong feminist ideals and impressive writing that’s bound to captivate.” – The Los Angeles Times   In the Society, Officials decide. Who you love. Where you work. When you die. Cassia has always trusted the Society to make the right choices for her: what to read, what to watch, what to believe. So when Xander's face appears on-screen at her Matching ceremony, Cassia knows with complete certainty that he is her ideal mate . . . until she sees Ky Markham's face flash for an instant before the screen fades to black. The Society tells her it's a glitch, a rare malfunction, and that she should focus on the happy life she's destined to lead with Xander. But Cassia can't stop thinking about Ky, and as they slowly fall in love, Cassia begins to doubt the Society's infallibility and is faced with an impossible choice: between Xander and Ky, between the only life she's known and a path that no one else has dared to follow. Look for the sequel, CROSSED , and the epic series finale, REACHED !